2015
DOI: 10.1007/s40732-015-0127-2
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Naming Relations and Intraverbals After Auditory Stimulus Pairing

Abstract: We analyzed the emergence of intraverbals, tacts, and selection in response to names spoken by the experimenter as a result of observing auditory stimulus pairing in 12 typical developing adults randomly assigned to two experimental and one control condition. In Part 1, four sounds of musical instruments were paired with their respective names spoken by the experimenter; in Part 2, the sounds were paired with their native country names spoken by the experimenter. Participants in Condition 1 received the pairin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 36 publications
2
14
0
3
Order By: Relevance
“…Until now, research related to compound stimuli has shown better performance when participants have had a learning history with these compound stimuli (see Alonso‐Álvarez, 2010; Alonso‐Álvarez & Pérez‐González, 2006; Alós et al, 2013; Guerrero et al, 2015; Maldonado et al, 2020; Pérez‐González & Alonso‐Álvarez, 2008). If the results found here are confirmed, the mere teaching of simple stimuli (the present experiment) or paired stimuli (Carnerero & Pérez‐González, 2015; Carnerero et al, 2019) could allow for learning to transfer to new operants with simple or compound stimuli. However, it is still necessary to examine the influence of easy‐to‐classify stimuli on learning outcomes.…”
Section: Resultssupporting
confidence: 56%
See 3 more Smart Citations
“…Until now, research related to compound stimuli has shown better performance when participants have had a learning history with these compound stimuli (see Alonso‐Álvarez, 2010; Alonso‐Álvarez & Pérez‐González, 2006; Alós et al, 2013; Guerrero et al, 2015; Maldonado et al, 2020; Pérez‐González & Alonso‐Álvarez, 2008). If the results found here are confirmed, the mere teaching of simple stimuli (the present experiment) or paired stimuli (Carnerero & Pérez‐González, 2015; Carnerero et al, 2019) could allow for learning to transfer to new operants with simple or compound stimuli. However, it is still necessary to examine the influence of easy‐to‐classify stimuli on learning outcomes.…”
Section: Resultssupporting
confidence: 56%
“…1) and only visual (Exp. 2 and 3), thus continuing the line of study followed by Carnerero and Pérez‐González (2015), Carnerero et al (2019) and Guerrero et al (2015). As a result, this research aims to contribute toward the study of relational learning, providing new data on how to present several types of stimuli to promote the autonomous grouping of categories by each individual without explicit training.…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…Training sequence effects have previously been found in research on the inclusion of meaningful stimuli in equivalence classes (e.g., Arntzen, ; Nartey, Arntzen, & Fields, ). In addition, Carnerero and Perez‐Gonzales () found that when baseline training involved class‐consistent contiguous presentation of stimuli, subsequent emergence of vocal intraverbal relations depended on the sequence in which baseline relations were presented. In general, however, such effects have not been studied systematically.…”
Section: Discussionmentioning
confidence: 99%